A corpus-based analysis of frequently occurring noun collocations in Geographical Information System (GIS) research articles - Ang, Leng Hong (Penerbit Universiti Kebangsaan Malaysia, 2023)
The importance of collocations in language learning cannot be overstated, particularly with successful academic writing. Previous research on collocation compilation has focused on identifying and compiling lists of general multiword expressions (MWEs) found in academic genres for pedagogical purposes. However, the wide-angle approach employed by these studies may be insufficient for English for Specific Purposes (ESP) courses, given certain formalities and conventions associated with academic texts, which are often demonstrated through MWEs unique to each field or domain of study. This paper presents a corpus-based investigation to develop a list of commonly and pedagogically useful noun collocations specific to the Geographical Information System (GIS). The research used a corpus containing 1.5 million words from GIS research articles. An innovative four-step selection process was used to compile this list. The outcomes of this study are twofold. First, the collocations associated with the 20 most frequently encountered nouns (including noun + noun, noun + verb, verb + noun, and adjective + noun combinations) within the GIS research articles were identified. Second, this investigation presented fresh insights into the different categories of noun collocations. The research provides important pedagogical implications for ESP instruction, particularly on how collocations might be better understood and taught. The findings emphasise the necessity of focusing on domain-specific collocations, underscoring the role of context in language learning and teaching. The results are expected to help shape effective instructional strategies and material development in ESP classrooms, particularly in GIS-related contexts.